The Lewis and Clark Expedition - Harris, Beatrice, 1978- (Look at US history., 2022)
Explores the events of Lewis and Clark's expedition to map a course to the Pacific Ocean, and profiles important people involved in the expedition. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.